Consistency and Homogeneity Test of Rainfall Data for The Payakumbuh City Area - Melvi Fathia Marisca; Ridha Sari; Biota Fotrah (Fakultas Teknik Sipil dan Perencanaan, 2026)
Rainfall plays an important role in planning water structures, be it drainage, irrigation, dams, etc. Testing rainfall data is useful for reducing the risk in planning water structures to be built. The rainfall data used was obtained from the PSDA of West Sumatra Province with 3 closest station points for the Pyakumbuh City area (Canduang Station, Tanjung Pati Station, and Suliki Station) over a period of 10 years (2013-2022). The RAPS and Double Mass Curve methods were used for consistency tests, while the T-test was used for Homogeneity tests. The results of the Double Mass Curve Consistency test at Suliki Station showed that the rainfall data was consistent, while at Tanjung Pati Station and Canduang Station it was inconsistent, so a correction factor was needed so that it was obtained at both stations consistent. While the consistency test U used RAPS method against preliminary rainfall data and that has been corrected obtained data results already consistent with mark as following : Q count < Q critical = 1.48 < 3.60. Q count < Q critical = 1.92 < 3.60. Q count < Q critical = 2.14 < 3.60. Q count < Q critical = 1.87 < 3.60. Q count < Q critical = 1.75 < 3.60. Meanwhile, the results of the RAPS method Consistency test show that the rainfall data from the three stations are consistent throughout the observation period. For the results of the Homogeneity test using t-test is as as follows : t count < t critical = 1.168 < 1.734. t count < t critical = 0.721 < 1.73. t count < t critical = 0.435 < 1.734. t count < t critical = 0.387 < 1.734. t count < t critical = 1.702 < 1.734. t count < t critical = - 0.071 < 1.734. From the calculation of the Homogeneity test of the t-test method, it shows that the rainfall data from the three rainfall stations did not experience significant changes throughout the time period, indicating that the data from the three rainfall stations were homogeneous. The results of the consistency test and homogeneity test showed that the rainfall data from the PSDA of West Sumatra Province were consistent and homogeneous.